Clinical and Molecular Characteristics of 60 Patients With Human Immunodeficiency Virus-Negative Castleman Disease - Qian, Siyu; Ding, Mengjie; Hou, Huting; Wang, Zeyuan; Zhang, Jieming; Zhang, Yue; Dong, Meng; Zhu, Linan; Wang, Guannan; Li, Wencai; Zhang, Xudong (Frontiers in Immunology, 2022)
Castleman disease (CD) is a rare lymphoproliferative disorder with low prevalence. The mechanistic target of rapamycin (mTOR) pathway is a key regulator of various cellular functions, which may be related with the potential mechanisms of CD occurrence. We retrospectively collected the clinical information of 60 CD patients diagnosed in the First Affiliated Hospital of Zhengzhou University. And PEEP biopsy specimens were collected from 31 patients (12 UCD patients and 19 MCD patients) to detect the mTOR pathway protein expression. The conclusion that thrombocytopenia was the independent poor prognostic factor for CD was first proposed, as well as elevated uric acid levels, hypoalbuminemia. And the activity of the mTOR pathway was higher than reactive lymphoid hyperplasia which served as control group, and some UCD specimens were tested positive. This study offers some elucidation for the management and treatment of CD patients.